Policies and programs for sustainable energy innovations renewable energy and energy efficiency - Daim, Tugrul Unsal 1967-; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This volume features research and case studies across a variety of industries to showcase technological innovations and policy initiatives designed to promote renewable energy and sustainable economic development. The first section focuses on policies for the adoption of renewable energy technologies, the second section covers the evaluation of energy efficiency programs, and the final section provides evaluations of energy technology innovations. Environmental concerns, energy availability, and political pressure have prompted governments to look for alternative energy resources that can minimize the undesirable effects for current energy systems. For example, shifting away from conventional fuel resources and increasing the percentage of electricity generated from renewable resources, such as solar and wind power, is an opportunity to guarantee lower CO2 emissions and to create better economic opportunities for citizens in the long run. Including discussions of such of timely topics and issues as global warming, bio-fuels, and nuclear energy, the editors and contributors to this book provide a wealth of insights and recommendations for sustainable energy innovations.
Preface -- Ch 1 Review of Policies Towards the Acceleration of the Adoption of Renewable Energy Technologies -- Ch 2 Renewable Energy Technology Adoption in the Pacific Northwest -- Ch 3 Evaluating Polices Towards the Adoption of Renewable Energy Technologies -- Ch 4 Assessment of Wind Potential in Kalar Kahar Region by Comparing On-Site Data with NREL Wind Resource Map of Pakistan -- Ch 5 Technological Assessment of Emerging Technologies in Conversion of Municipal Solid Waste of Energy -- Ch 6 Bio-fuel Adoption -- Ch 7 Assessing Alternatives for District Heating -- Ch 8 Technology Adoption -- Ch 9 Portfolio Optimization in the Electricity Market-Investor's Perspective -- Ch 10 Energy Efficiency Technologies -- Ch 11 Evaluating Energy Efficiency -- Ch 12 Evaluating Consumer Preferences for Clothes Dryers -- Ch 13 Technology Intelligence on Clothes Dryers -- Ch 14 Furnace Fan Motor Technology Assessment -- Ch 15 Technology Assessment of Insulation Material for Home Construction.
Electronic reproduction.
Keywords: Renewable energy sources -- Government policy; Energy industries -- Technological innovations; Technological innovations -- Government policy; Electronic books